Experiência da morte como experiência de vida: coveiros, “observadores privilegiados da despedida” - Viana, Anderson Boás (2021)
This dissertation aims to present the universe of Gavião Cemetery, based on the narratives of the professionals who work there. Therefore, we chose as research subjects the gravediggers, also known as buriers - professionals who carry the stigmas of a discriminated, rejected and invisible profession in the eyes of society, although paradoxically considered an essential profession by the same society. Having defined the object of study, this research investigates the relation between the gravedigger's profession, deeply stigmatized in the popular imagination, and the reified stigmas in contemporary western society about death, about dying and about the cemetery itself. In this study, therefore, we present and analyze the issues of everyday life and the meanings constructed by the gravediggers who experience that routine (space/time). Throughout the chapters, enriched with photographs and, specially, narratives, trivial practices, gestures, facial expressions and the operational routine of their work are observed, allowing us to know histories and stories so far unheard of . For a better understanding of the proposal of this dissertation, its construction took place in five chapters. Thus, after the introduction, the theme's unfolding is addressed, noticing in the narratives issues such as perception of stigmas, the way of working and daily organization, the films and literature that confirm the stigmatized image of the cemetery and the professionals who work there, and the affective relationships established in that environment. In chapter three, the specificities of the Gavião Cemetery are discussed, not based on a literary description, but based on the gravediggers' perception of the place, its characteristics, cemetery art and legends. The fourth chapter presents a critical analysis of this cemetery as a place of memory and ritualization practices. For this, we list different authors who deal with the theme and present the rituals perceived daily in the cemetery. Also, it was possible to reflect on the rituals during a pandemic and how this period has affected the routine in/of the cemetery. To conclude the research, the final considerations are presented in a reflective way about the avenues and observations in the field. It is noticed that the Cemetery is a place of different interpretations, an integral part of the conscience of a society, therefore, paradoxically, a place of life.